Impact of Globalization and Renewable Energy Consumption on Environmental Degradation: A Lesson for South Africa - Seun Damola Oladipupo; Husam Rjoub; Dervis Kirikkaleli; Tomiwa Sunday Adebayo (International Journal of Renewable Energy Development, 2022)
South Africa is one of Africa's most polluted countries, with rising CO2 emissions posing a threat. South Africa must discover ways of minimizing pollution and take necessary steps before it is too late in order to achieve sustainable growth. For this purpose, this research assesses the ecological consequences of globalization, nonrenewable energy use, economic growth and renewable energy consumption in South Africa. The study leverages on the non-linearity advantages of the novel quantile on quantile regression (QQR) method for a robust analysis as opposed to the use of conventional linear approaches, thereby overcoming conspicuous shortfalls in extant studies, while offering a detailed explanation of the overall dependency structure between CO2 emissions and globalization, nonrenewable energy use and renewable energy use using a dataset covering the period between 1970 and 2018. The outcomes suggest that nonrenewable energy use, globalization, and economic growth contribute to environmental degradation in the majority of the quantiles, while the effect of renewable energy use on CO2 is not strong at all quantiles. The study highlights that economic expansion, nonrenewable energy use and globalization play key roles in in mitigating environmental sustainability in South Africa, while renewable energy is not sufficient to meet environmental requirements.